The shorter Oxford English dictionary on historical principles (Oxford Clarendon Press, 1973)
The Shorter Oxford English Dictionary is an important and authoritative reference work for modern English. It incorporates a complete vocabulary update with over 3,500 new words and meanings, and many new illustrative quotations from modern authors. I n total there are over 83,000 illustrative quotations from 7,000 authors. There is extensive coverage of scientific and technical English as well as English from around the world. The Dictionary is written on historical principles: entries show the historical development of words by listing meanings chronologically and giving dates for the first use of each sense. All major words used in English after 1700, as well as all the words in Shakespeare, Milton, Spenser's Faerie Queene, and the King James Bible, are included; many rare and obsolete words are also defined.
v. 1. A-Markworthy -- v. 2. Marl-Z and addenda.
"An abridgement officially authorized by the Delegates of the Oxford University Press of A new English dictionary on historical principles, later known as The Oxford English dictionary"--P. [vii].
Keywords: English language -- Dictionaries; English language -- Etymology -- Dictionaries